Epidemiology and clinical outcomes of octogenarian patients in an intensive care unit from a developing country (2010)
Around the world, the elderly population is growing faster than the total population, and this difference in growth rates is increasing [1]. In 1950, 1 in every 20 individuals was aged 65 years or older; by the year 2050, this figure is projected to increase to nearly 1 in 6 (Fig. 1) [1]. These population trends represent a looming crisis for healthcare systems around the world, and understanding patterns of care and outcomes for the ageing segment of the population is vital when planning for future healthcare needs in all countries.